Transformasi Perpustakaan Konvensional Menjadi Smart Library Dengan Teknologi Pemindaian Cepat Di SMK Negeri 1 Percut Sei Tuan - Syahputra, Fahmy; Lubis, Azmi Rizki; Dalimunthe, Amirhud; Adhitya, Wisnu Rayhan; Pratama, Saras (Cattleya Darmaya Fortuna, 2025)
The advancement of information technology has brought significant changes to library management, shifting from conventional systems toward the Smart Library concept, which is more modern, efficient, and interactive. This study aims to implement fast-scanning technology based on QR Code and RFID in the management system for book collections, borrowing, and returning processes at SMK Negeri 1 Percut Sei Tuan. The research adopts a Research and Development (R&D) approach using the prototyping model, which includes stages of needs analysis, system design, implementation, and limited testing within the school environment. The implementation results show an increase in library service efficiency by up to 65% compared to the manual method, along with a reduction in recording errors and improved convenience for students in locating and borrowing books. Therefore, the application of a Smart Library system utilizing fast-scanning technology has proven to be effective and feasible as an innovative digital solution to support the transformation of library services in vocational schools